2015
DOI: 10.1007/s40830-015-0044-x
|View full text |Cite
|
Sign up to set email alerts
|

Computational Thermodynamics and Kinetics-Based ICME Framework for High-Temperature Shape Memory Alloys

Abstract: Over the last decade, considerable interest in the development of High-Temperature Shape Memory Alloys (HTSMAs) for solid-state actuation has increased dramatically as key applications in the aerospace and automotive industry demand actuation temperatures well above those of conventional SMAs. Most of the research to date has focused on establishing the (forward) connections between chemistry, processing, (micro)structure, properties, and performance. Much less work has been dedicated to the development of fra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 130 publications
(198 reference statements)
0
1
0
Order By: Relevance
“…The application scope of SMAs is broad across various sectors such as the automotive, aerospace, manufacturing, and energy exploration sectors [25]. Recently, it has been shown that control of the distribution of secondary strengthening precipitate phases in some SMAs can enable further control strategies to tune their transformation behavior to specific engineering applications [16,26].…”
Section: Introductionmentioning
confidence: 99%
“…The application scope of SMAs is broad across various sectors such as the automotive, aerospace, manufacturing, and energy exploration sectors [25]. Recently, it has been shown that control of the distribution of secondary strengthening precipitate phases in some SMAs can enable further control strategies to tune their transformation behavior to specific engineering applications [16,26].…”
Section: Introductionmentioning
confidence: 99%